La ironía del dispositivo y el mayo del 68 francés: The irony of the device and the French May 68 - SERRANO, Vicente (Utopía y Praxis Latinoamericana, 2021)
RESUMEN  Este artículo presenta la propuesta de Foucault de repensar las raíces de la sociedad capitalista en relación con la subjetividad, el deseo y el poder. La hipótesis es que en el fondo Foucault no considera al mayo del 68 un acontecimiento revolucionario, sino más bien un acontecimiento que saca a la luz ese nuevo tipo de dominio que con el tiempo llamará biopolítico, aquel ABSTRACT This article presents Foucault's proposal to rethink the roots of capitalist society in relation to subjectivity, desire and power. The hypothesis is that, deep down, Foucault does not consider May '68 a revolutionary event, but rather an event that brings to light that new type of domain that he will call biopolitical over time, one in which the satisfaction of the governed results the key and that is expressed in terms of that irony of the device.